2021
DOI: 10.3390/jcm10225327
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Global Postural Re-Education in Chronic Non-Specific Low Back Pain: Systematic Review and Meta-Analysis

Abstract: Background: The aim of this systematic review and meta-analysis was to evaluate the global postural re-education (GPR) program’s effectiveness compared to other exercise programs in subjects with persistent chronic low back pain. Methods: A systematic review and meta-analysis were carried out using PRISMA2020. An electronic search of scientific databases was performed from their inception to January 2021. Randomized controlled trials that analyzed pain and patient-reported outcomes were included in this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…With the same follow up, GPR sessions show better results in flexibility than an analytic stretching program [26] and an important reduction of pain. Several other clinical trials have evaluated the effects of GPR treatments measuring low back pain, neck pain, quality of life, or evaluating disability questionnaires, with strong evidence of GPR as an effective method for treating spinal disorders [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…With the same follow up, GPR sessions show better results in flexibility than an analytic stretching program [26] and an important reduction of pain. Several other clinical trials have evaluated the effects of GPR treatments measuring low back pain, neck pain, quality of life, or evaluating disability questionnaires, with strong evidence of GPR as an effective method for treating spinal disorders [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Past intervention studies have indicated that single postural re-education intervention can reduce pain and disability in acute and chronic low back pain patient [ 64 , 65 ]. This result is consistent with the recent meta-analysis on postural re-education for CLBP [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al [6] concluded that physical inactivity could explain this functional limitation and stressed the importance of following a programme of physical activity. In this respect, a global postural re-education program is effective compared to other exercise programmes in subjects with persistent chronic low back pain [71].…”
Section: Functional Limitationmentioning
confidence: 99%